Ocena składników sfer potencjału rozwojowego gmin (na przykładzie powiatu zambrowskiego) - Krukowski, Krzysztof (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main objective of the article was the identification of factors determining the development potential of local communes on the example of zambrowski powiat (podlaskie province).To evaluate the strategic potential of the commune it was divided into 13 strategic fields. The biggest impact on local development has technical infrastructure due to the survey, and also the field of management of local commune. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 325-332